2019
DOI: 10.35794/jmbi.v6i1.24270
|View full text |Cite
|
Sign up to set email alerts
|

Optimalisasi Potensi Pajak Dan Retribusi Dalam Meningkatkan Pendapatan Asli Daerah (Pad) Kota Ambon

Abstract: Since Indonesia implemented regional autonomy, part of the financial authority was delegated to the regions so that the regions could independently optimize their regional financial potential, mainly from taxes and levies as their main source of income. Ambon City as an area that has long implemented autonomy still faces the problem of how to optimize the potential of PAD, especially through taxes and levies. This study aims to analyze strategies for optimizing taxes and levies in Ambon City. This study uses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…To moderate these two opinions, various solutions emerged, one of which was Devas' opinion. 22 Devas proposed five benchmarks for assessing regional tax, i.e. yield, equity, economic efficiency, ability to implement, and suitability as a local source.…”
Section: Regional Tax Regulationsmentioning
confidence: 99%
“…To moderate these two opinions, various solutions emerged, one of which was Devas' opinion. 22 Devas proposed five benchmarks for assessing regional tax, i.e. yield, equity, economic efficiency, ability to implement, and suitability as a local source.…”
Section: Regional Tax Regulationsmentioning
confidence: 99%
“…In various studies, literature and existing reports, it is revealed that there are still many types of regional income sources that have not been managed properly, while those that have not been managed optimally. Among other things, the results of a study by the Department of Home Affairs on 26 regencies and cities in Indonesia found that the value of fees has not benefited the region because they do not yet have encouraging prospects (Tupamahu et al, 2019) [4].…”
Section: Introductionmentioning
confidence: 99%